The Cultural Approach in Promoting Agricultural Emigration to Lampung in Java 1931-1940 - Mutiara Agustina; Abd Rahman Hamid; Aan Budianto (Universitas Islam Negeri Sumatera Utara, 2026)
This study aims to explain the promotion of emigration of the Javanese people to Lampung using a cultural approach. There are two main issues in this article: first, how early emigrants who had already settled in Lampung promoted the overseas land (tanah sabrang) in Java; second, how the Javanese cultural approach could attract the interest and trust of the Javanese people to emigrate. The method used in writing this article is the historical method, which includes the stages of heuristics, source criticism, interpretation, and historiography, thus producing a historical narrative that is chronological, causal, and imaginative. The results of this research show that the cultural approach through sending back Javanese who had previously migrated to Lampung to return to Java, staging ketoprak performances, sending gamelan to Lampung as gifts, and featuring wayang figures in films about tanah sabrang, successfully captured the attention of the Javanese people and had a significant positive impact on the trust level of prospective emigrants who were to be relocated to the emigration land in Lampung.